Effect of Variable Properties on the Flow Past a Needle Moving in a Casson Fluid - Srinivasacharya, D.; Saritha, G. (Discontinuity, Nonlinearity, and Complexity, 2026)
This work considers the flow past a horizontally moving needle submerged in Casson fluid. The viscosity and thermal conductivity are assumed to be dependent on temperature. The flow-governing equations are changed into a set of non-linear ordinary differential equations using appropriate transforms. Applying successive linearization, the resulting equations are linearized, and then the Chebyshev spectral collocation technique is implemented. The effects of the Casson fluid parameter, needle size, and viscosity parameter on velocity and temperature, along with graphical representations of the coefficient of skin friction and local heat transfer rate, are presented graphically. It is observed that an enhancement in the viscosity parameter results in a decrease in the heat transfer rate and an increase in velocity. Temperature, velocity, and heat transfer rate all increase as the thermal conductivity parameter increases.